76‐3: Ultra‐High‐Efficiency OLED Display by 3D Pixel Configuration. Issue 1 (25th September 2020) - Visser, Robert Jan; Chen, Chung-Chia; Bang, Hyunsung; Lin, Wan-Yu; Xu, Lisong; Yu, Gang; Kwak, B. Leo; Chen, Yi-Ting; Wen, Sheng-Wen; Liao, Po-Hsiang; Lee, Chang-Cheng; Lee, Wei-Kai; et al.
Abstract : Exploring beyond our previously published work on 3D pixel configuration for high light out‐coupling in OLED devices, we will report on configurations wherein the transparent conductive oxide is the top electrode. This can lead to substantially greater EQE (> 3.5x) over the current baseline OLED, by combining it with the previously‐reported patterned, index‐matched filler and the reflective mirror on PDL bank. In addition, we will report on simulation work that expands beyond the pixel level to include the functional layers, e.g., TFE, touch, OCAs, and polarizer, above the pixel. Such results will elucidate the full, device‐level impact of the novel 3D OLED subpixel architectures and instructions on design principles for maximum OLED device performance.